Isolated Nasopharyngeal Castleman Disease: An Uncommon Diagnosis in an Unusual Location - O. McDonnell; Melinda Morris; Z. Khaleel (Case Reports in Radiology)
Localised nasopharyngeal Castleman disease has rarely been reported. We present a case involving a 23-year-old female, describe the clinical, imaging, and histopathologic features of this challenging diagnosis, and review the literature.